Pengaruh Teknik Rebozo Terhadap Posisi Janin Dan Nyeri Persalinan Pada Ibu Hamil Trimester Akhir Di Puskesmas Pebayuran Tahun 2025 - Eliya Winta Marlina; Mariyani Mariyani (Jurnal Ners, 2026)
Background: Labor pain and suboptimal fetal positions, specifically the Occiput Posterior (OP) position, represent significant physiological and obstetrical challenges for women in the third trimester of pregnancy. Unmanaged pain can precipitate prolonged labor, increase maternal stress hormones, and elevate the risk of medical interventions such as instrumental delivery or cesarean section. The Rebozo technique is a traditional non-pharmacological intervention originating from Mexico that utilizes a woven shawl (jarik) to perform specific rhythmic movements, sifting and shaking, on the maternal pelvis. This technique aims to relax the pelvic ligaments and uterine muscles, thereby facilitating optimal fetal rotation and reducing pain perception. Objective: This study aims to extensively analyze the effect of the Rebozo technique on optimizing fetal position and reducing the intensity of labor pain in third-trimester pregnant women at Pebayuran Public Health Center. Research Method: The study employed a quantitative research method with a Quasi-Experimental Pre-test Post-test with Control Group Design. The population comprised all third-trimester pregnant women (≥37 weeks) at the study site, with a sample of 30 respondents selected via Total Sampling. Instruments included Leopold maneuver observation sheets for fetal positioning and the Numeric Rating Scale (NRS) for pain assessment. Data were analyzed using univariate analysis and the Wilcoxon Signed Rank Test for bivariate comparison including Effect Size calculation. Research Result: Baseline data indicated that prior to intervention, 53.33% of respondents experienced severe pain and 46.67% experienced moderate pain. Following the Rebozo intervention, there was a statistically significant reduction in pain intensity, with the majority of the intervention group reporting reduced pain levels. The Wilcoxon Signed Rank Test yielded a p-value of 0.001 (< 0.05) and a Z-score of -3.462, with a strong Effect Size (r = 0.89). Qualitative observations also confirmed improvements in fetal positioning and maternal comfort. Conclusion: The application of the Rebozo technique has a significant positive effect on reducing labor pain intensity and facilitating optimal fetal positioning in third-trimester pregnant women. It is a viable, low-cost, and effective complementary care model for midwifery practice.